2015
DOI: 10.1097/j.pain.0000000000000192
|View full text |Cite
|
Sign up to set email alerts
|

Experimental reduction of pain catastrophizing modulates pain report but not spinal nociception as verified by mediation analyses

Abstract: Pain catastrophizing is associated with enhanced pain; however, the mechanisms by which it modulates pain are poorly understood. Evidence suggests that catastrophizing modulates supraspinal processing of pain but does not modulate spinal nociception (as assessed by nociceptive flexion reflex [NFR]). Unfortunately, most NFR studies have been correlational. To address this, this study experimentally reduced catastrophizing to determine whether it modulates spinal nociception (NFR). Healthy pain-free participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 45 publications
2
50
0
Order By: Relevance
“…In addition, the level of change in catastrophizing was associated with the change in pain, which is suggestive of a direct pain-enhancing mechanism [62]. Moreover, a reduction in catastrophizing led to reductions in pain report in healthy individuals, which was found to be modulated at the supraspinal level [63]. Finally, providing failure feedback to healthy participants, which may be similar to creating a feeling of helplessness, has been shown to lead to an increase in pain reports [64].…”
Section: Experimental Studiesmentioning
confidence: 82%
“…In addition, the level of change in catastrophizing was associated with the change in pain, which is suggestive of a direct pain-enhancing mechanism [62]. Moreover, a reduction in catastrophizing led to reductions in pain report in healthy individuals, which was found to be modulated at the supraspinal level [63]. Finally, providing failure feedback to healthy participants, which may be similar to creating a feeling of helplessness, has been shown to lead to an increase in pain reports [64].…”
Section: Experimental Studiesmentioning
confidence: 82%
“…This is consistent with numerous studies showing that pain catastrophizing is associated with pain facilitation (eg, Refs 23,56,57) and extends this work to demonstrate that experimental reductions in pain catastrophizing leads to a reduction in pain. 59 Furthermore, formal mediation analysis found that the reductions in pain intensity and unpleasantness were at least partially mediated by the reductions in pain catastrophizing. Given that changes in catastrophizing were experimentally manipulated, this provides evidence that pain catastrophizing can produce pain facilitation and that reducing catastrophizing can reverse this facilitation.…”
Section: Threat-evoked Amplification Of Pain and Nociceptive Flexion mentioning
confidence: 99%
“…57 Like our previous studies, 46,47,59 the PCS was administered using modified instructions to assess situation-specific catastrophizing ("Thinking back to your experience during the electric stimulations, please indicate the degree to which you had these thoughts and feelings"). This allowed us to eliminate participants who did not catastrophize at baseline and to evaluate changes in pain catastrophizing that resulted from the cognitivebehavioral techniques.…”
Section: Pain Catastrophizingmentioning
confidence: 99%
See 1 more Smart Citation
“…5,37,39,41,50 The assessment of altered central pain processing using quantitative sensory testing typically includes the measurement of pain intensity or pain thresholds after the application of painful stimuli. 39,41 However, the perception of pain is subjective, which may cause unwanted variation in test results depending on various factors that are difficult to control during the assessment, such as catastrophizing, 18,42,43,52 cognitive attention, 7 and hormonal status. 19 Novel methods based on more objective parameters would be desirable.…”
Section: Introductionmentioning
confidence: 99%